The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1136/bmjopen-2018-026947
|View full text |Cite
|
Sign up to set email alerts
|

Better evidence: prospective cohort study assessing the utility of an evidence-based clinical resource at the University of Rwanda

Abstract: ObjectiveEvidence-based clinical resources (EBCRs) have the potential to improve diagnostic and therapeutic accuracy. The majority of US teaching medical institutions have incorporated them into clinical training. Many EBCRs are subscription based, and their cost is prohibitive for most clinicians and trainees in low-income and middle-income countries. We sought to determine the utility of EBCRs in an East African medical school.SettingThe University of Rwanda (UR), a medical school located in East Africa.Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Though medical students in the US are likely to be introduced to these digital tools early in their career 6 , the use of digital tools has not gained the same momentum in sub-Saharan African medical education 7 . Research conducted by the authors of this study at the University of Rwanda suggests that early introduction of an evidence-based tool to medical students leads to habit formation and use of the tool in later clinical practice 8 . However, there has been limited research on this topic, likely due to limited access to such tools whose cost can be prohibitive.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Though medical students in the US are likely to be introduced to these digital tools early in their career 6 , the use of digital tools has not gained the same momentum in sub-Saharan African medical education 7 . Research conducted by the authors of this study at the University of Rwanda suggests that early introduction of an evidence-based tool to medical students leads to habit formation and use of the tool in later clinical practice 8 . However, there has been limited research on this topic, likely due to limited access to such tools whose cost can be prohibitive.…”
Section: Introductionmentioning
confidence: 87%
“…Chan School of Public Health and Brigham and Women's Hospital – works to facilitate access to evidence-based clinical resources to health providers serving vulnerable populations who couldn't otherwise afford them. A pilot study run by Better Evidence demonstrated the utility of Up-To-Date among medical students at University of Rwanda 8 , the group began facilitating donated institutional licenses to medical schools across Africa as part of the Better Evidence for training program. Access was granted to MakCHS in 2019, with plans to add new schools annually.…”
Section: Accessing Uptodatementioning
confidence: 99%
“…There is often a difference in the health policy of LMICs between the government’s perceived priorities and what the population wants [32]. Guidelines have helped the standardisation of care and improved standards in many HICs [33], but have been shown to negatively influence their uptake in situations different from where the data were derived [34]. This difficulty in characterisation of disease prevalence between LMICs and HICs means that the utility of urological guidelines, outside the environment they were formulated in becomes a significant issue.…”
Section: Appropriatenessmentioning
confidence: 99%
“…The potential for their development does exist as there are several associations that could constitute member committees to formulate them and initiate data collation; the Pan‐African Association of Urology, The South African Urology Association, Urological Association of Zambia, and the Egyptian Urological Association all have this capacity. If they developed context‐based, local and regional guidelines, available from a freely available open‐access source [34], an increased uptake of locally relevant data would possibly encourage the provision of a more evidence‐based practice [34, 35].…”
Section: Appropriatenessmentioning
confidence: 99%
“…Therefore, during the 2015-2016 year, the educational committee organized a new intervention FD module emphasizing leadership. Case-control studies sometimes use historical controls, if controls are not permitted, based on special conditions such as the learning right of participants and educational ethics [22,23]. Therefore,, historical regular FD cohorts were used in this study between 2013 and 2016 as controls for the intervention FD cohorts.…”
Section: Background To the Development Of The New Leadershipenhanced mentioning
confidence: 99%